The CLAVATA3/ESR-related peptide family in the biofuel crop pennycress - Hagelthorn, Lynne; Fletcher, Jennifer C. (Frontiers in Plant Science, 2023)
CLAVATA3/ESR-related (CLE) peptides perform a variety of important functions in plant development and historically have been targeted during the domestication of existing crops. Pennycress (Thlaspi arvense) is an emerging biofuel crop currently undergoing domestication that offers novel monetary and environmental incentives as a winter cover crop during an otherwise fallow period of the corn/soybean farming rotation. Here we report the characterization of the CLE gene family in pennycress through homology comparison of the CLE motif with other dicot species by conducting a homology comparison and maximum likelihood phylogenetic analysis supplemented with manual annotation. Twenty-seven pennycress CLE genes were identified, and their expression analyzed through transcriptome profiling and RT-qPCR. Our study provides a genome-wide analysis of the CLE gene family in pennycress and carries significant value for accelerating the domestication of this crop through identification of potential key developmental regulatory genes.